http://i26.tinypic.com/216kqr.jpg
^It's all there
Thanks!
http://i26.tinypic.com/216kqr.jpg
^It's all there
Thanks!
Hello!
You are right, a) and c) (that is answer d :-) is correct)
Of course b is not correct.
You know that answer a) is correct and probably you know that the solution is -7, but what matters is that $\displaystyle \lim_{x \to -3+ }f(x) = \lim_{x \to -3- }f(x)$ (thats answer a) )
Using that answer, how is answer b) : $\displaystyle \lim_{x \to -3+ }f(x) = -\lim_{x \to -3- }f(x) $right?
That's nuts ; assuming b) is correct, it is $\displaystyle \lim_{x \to -3+ }f(x) = -\lim_{x \to -3- }f(x) = \lim_{x \to -3- }f(x) $, e. g. $\displaystyle -\lim_{x \to -3- }f(x) = \lim_{x \to -3- }f(x)$ : If the limes of f(x) is '0' it would have been correct : But it's not!
Yours
Rapha
Hi again.
Just consider the solutions of answer a,b,c
a)
$\displaystyle -7=\lim_{x\to -3^+} f(x)= \lim_{x\to -3^-}f(x)=-7$
b)
$\displaystyle -7 = \lim_{x\to -3^-} f(x)\not= -\lim_{x\to -3^+} f(x) = -(-7) = +7 $
You still have a -7 on the left side.
c)
$\displaystyle -7= \lim_{x\to -3^-} f(x) = \lim_{x\to -3^+}f(x) =-7$
I'm sorry but I'm still not getting your logic..I'm not sure why you changed most of the signs in each answer choice. I'm not sure if you did it by accident or on purpose, but I don't get why.
For example, in choice b, it's:
x-->3- and then on the other side, x-->3+
I still can't see why my reasoning is wrong... +7 = -(-7)
You put: -3- and -3+
For c:
-3- and 3+ (but you put -3+)
I understand why when you actually plug in -3 or 3, but I was getting confused because I was also viewing the graph, and thinking that the big u shape in the middle was also approaching positive 7 but I guess not. I thought I had to use the graph to see what its approaching from the left or right side. Can I just do it mathematically?